P73 Implications and outcomes of clinical and radiological incidental lung cancer screening findings for primary care – results from a pilot screening study. (12th November 2019) - Bartlett, EC; Kemp, S; Derbyshire, J; Morris, K; Addis, J; Ridge, C; Mirsadraee, S; Padley, S; Desai, SR; Devaraj, A
Abstract : Background: Pilot lung cancer screening programmes in England have utilised a lung health check (LHC) model, comprising a nurse-led respiratory consultation, spirometry and a lung cancer risk calculation. We report the short-term outcomes of recommendations made to primary care for management of non-cancer incidental findings in a screening pilot. Methods: 1542 participants from 17 general practice (GP) surgeries attended for a LHC between August 2018 and April 2019. Lung nodules, significant incidental lung findings on computed tomography (CT), unexplained respiratory symptoms, and suspected non-lung malignancies were managed within the screening programme. Participants with: i) 'red-flag' symptoms without lung cancer, ii) unexplained obstructive spirometry and respiratory symptoms, iii) significant coronary artery calcification (CAC) on CT, who were not known to have previously undergone cardiovascular risk stratification, and iv) significant, but non-urgent, non-lung incidental findings on CT, were referred to primary care. GP records were evaluated to establish outcomes. Results: 165 primary care recommendations were made in 157/1542 (10.2%) individuals. Results below are from 16 GP practices and will be updated at the time of presentation. 49/1542 (3.2%) were referred to their GP for suspected undiagnosed chronic obstructive pulmonary disease (COPD), of whom 19/49 (38.8%) had a community-based respiratory review. 12/49 (24.5%) were newly diagnosed with COPD, and 5/49 (10.2%) commenced inhaler therapy. Of 52/1145 (4.5%) scanned participants with heavy CAC but without known ischaemic heart disease, 26/52 (50.0%) had a QRISK2 score (all >10%). Lipid-lowering therapy was commenced in 21/52 (40.4%). Echocardiography was recommended for 22/1542 (1.4%) participants with suspected cardiac disease, largely aortic valve calcification. 7/22 (31.8%) underwent echocardiography. Only 1/22 (4.5%) was deemed to require intervention for significant aortic stenosis. 7/1542 (0.5%) recommendations were made for other non-urgent/non-cardiothoracic incidental findings; none required further intervention. Conclusions: A minority of participants required primary care management for incidental findings based on the West London lung screening study protocol. Although not all recommendations were implemented, incidental findings infrequently led to changes to patient management overall. Changes to patient management most commonly occurred as a result of recommendations for assessment for COPD and cardiovascular risk.